2015
DOI: 10.1080/10426914.2015.1070416
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Vanadium-Microalloyed Medium-Carbon Steel by Optimizing Post-Forging Cooling Conditions

Abstract: The effects of different cooling conditions after forging on the microstructural characteristics and mechanical properties of a kind of high-content V-microalloyed medium-carbon steel 37MnSiVS were investigated. The effects were studied by using optical microscopy, transmission electron microscopy and tensile tests. Increasing direct cooling rate after forging is found to increase strength while slightly decrease ductility. A significant increase of strength could be obtained after forced air cooling and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 21 ] However, it was also reported that vanadium addition leads to an increase in prior austenite grain size, which was explained by an interaction between titanium nitrides and vanadium carbides. [ 22 ] Another explanation for increased hardenability is that vanadium, when present in solid‐solution, shifts the diffusion‐controlled phase transformation to slower cooling rates, [ 23 ] especially during continuous cooling. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] However, it was also reported that vanadium addition leads to an increase in prior austenite grain size, which was explained by an interaction between titanium nitrides and vanadium carbides. [ 22 ] Another explanation for increased hardenability is that vanadium, when present in solid‐solution, shifts the diffusion‐controlled phase transformation to slower cooling rates, [ 23 ] especially during continuous cooling. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The carbon atoms are easy to segregate at the phase boundaries . The deviation of carbon content between XRD and 3DAP data can be explained by the fact that the C content in retained austenite is determined by XRD under the simplified assumption that C segregating at dislocations does not occur . Moreover, the method with electromagnetic wave has low precision to measure intensity distribution of diffraction peak compared with 3DAP.…”
Section: Discussionmentioning
confidence: 99%
“…The alloying elements requirement of the TAM steel indicates that the chemical compositions similar to conventional TRIP‐assisted steels are appropriate . To investigate the precipitation behavior of V, different contents of V were added in the three experimental steels . The hot‐rolled steel sheets of 4 mm thickness were air cooled down to room temperature and cold rolled to the strip of 2 mm thickness after pickling in acid.…”
Section: Methodsmentioning
confidence: 99%
“…For every forging, post cooling rates decide the type of matrix structure, namely, quenching, rapid cooling, and moderate cooling resulting in martensite, bainite, and ferrite-pearlite matrix structures, respectively. Microalloying of V, Ti, and/or Nb contributes to the refining of prior austenitic grain and the precipitation strengthening of the matrix structure by V,Ti,Nb(C,N)-carbonitrides [8,[38][39][40][41][42][43][44][45]. Microalloying of Cr, Mo, Ni, B, etc.…”
Section: Classification Of Hot-forging Process For Low and Medium Carmentioning
confidence: 99%